2015
DOI: 10.1387/ijdb.150232dg
|View full text |Cite
|
Sign up to set email alerts
|

Human transient receptor potential (TRP) channel expression profiling in carcinogenesis

Abstract: Despite the intensive research of the last three decades into Transient Receptor Potential (TRP) cation channels, no precise and complete profiling of these channels is yet available regarding their involvement in physiopathology and carcinogenesis in particular. TRP channel activity is crucial for all the essential hallmarks of carcinogenesis such as proliferation, apoptosis, migration and angiogenesis, which is the reason why these channels have been proposed not only as clinical markers, but also as promisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 71 publications
(74 reference statements)
0
24
0
Order By: Relevance
“…Partial TRP expression profiles have appeared for a variety of murine tissues (35), including adipose (18). A comprehensive profile of TRP channel expression in human adipose tissues and associated progenitor cells is currently lacking (36). We analyzed the expression pattern of all human TRP channels during in vitro adipogenesis and found strong constitutive expression of TRPs P2, M7, V1, V2, V4, C1, C4, and ML1 in both MSCs and SVF cells, regardless of differentiation status, reflecting their generalized role in cell growth (proliferation and metabolism) and survival (37).…”
Section: Discussionmentioning
confidence: 99%
“…Partial TRP expression profiles have appeared for a variety of murine tissues (35), including adipose (18). A comprehensive profile of TRP channel expression in human adipose tissues and associated progenitor cells is currently lacking (36). We analyzed the expression pattern of all human TRP channels during in vitro adipogenesis and found strong constitutive expression of TRPs P2, M7, V1, V2, V4, C1, C4, and ML1 in both MSCs and SVF cells, regardless of differentiation status, reflecting their generalized role in cell growth (proliferation and metabolism) and survival (37).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, it has been shown that changes in the expression of TRP channels are correlated with the progression of different types of cancer. To date, most changes involving TRP proteins do not involve mutations in the TRP gene but rather dysregulation of the wild-type TRP protein expression levels, depending on the stage of cancer ( Gkika and Prevarskaya, 2011 ; Lehen’kyi and Prevarskaya, 2011 ; Bernardini et al, 2015 ; Shapovalov et al, 2016 ). Moreover, several recent studies have highlighted a direct correlation between cancer patient survival and TRP channel expression.…”
Section: Introductionmentioning
confidence: 99%
“…It follows that cells may experience different status, such as growth, differentiation, or death. Particularly, the abnormal conditions of ion channel trigged by mechanical force, that is, the abnormal switch on-off and excessive open or close, can induce cell apoptosis and death (see reviews [94][95][96]). It provides us with a new thought for cell regulation or diseases therapy.…”
Section: Under Constant or Low Frequency Magnetic Fieldmentioning
confidence: 99%